Design and Development of Syringe Needle Destroyer Using Melting Method - Ade Firdaus; Ferdana, Nanda; Mujakar, Samsul; Satrio, Hendrik; Zulhamidi (Universitas Muhammadiyah Surakarta, 2024)
Syringe needles are among the most commonly used medical tools in healthcare facilities across Indonesia, contributing significantly to medical waste. Improper disposal of syringe waste poses risks of disease transmission and potential misuse. Presently, small-scale beauty clinics resort to third-party waste management services due to the lack of incinerators. This research aims to develop a device capable of melting used syringe needles to ensure safe waste processing for both humans and the environment. Additionally, the objective is to create a low-budget needle destroyer, making it accessible to other healthcare services. The melting method is employed for needle destruction, utilizing a transformer to generate electrical current and heat. This approach offers ease of use and eliminates air, noise, and metal dust pollution. Through experimentation with various syringe sizes (1 cc, 3 cc, 5 cc, and 10 cc), it was found that melting times sequentially increase with needle size: 4 seconds for 1 cc, 5 seconds for 3 cc, 6 seconds for 5 cc, and 8 seconds for 10 cc syringes. This research contributes to sustainable healthcare waste management practices, ensuring safer and more affordable solutions for healthcare facilities